Sustainable and Smart Construction: Analysis of Mortars with PCR-PET Incorporation through Impact Acoustic Spectroscopy - Brandão, Raul de Souza; Oliveira, Gustavo dos Santos de; Abreu , Ramon Fernandes de; Lima, José Augusto Pedro; Alexandre, Jonas (National Journal of City Management, 2025)
Objective – To evaluate the performance of mortars with partial replacement of natural aggregate by post-consumer recycled polyethylene terephthalate (PET-PCR), using the Impact Acoustic Spectroscopy (IAS) technique, focusing on sustainability and technological innovation in the construction sector.Methodology – Mortar samples were prepared with different proportions of PET-PCR (10%, 20%, 30%, and 40%) replacing the natural aggregate. The samples underwent mechanical characterization (compressive and tensile strength) and acoustic analysis using the Impact Acoustic Spectroscopy (IAS) technique to assess behavior under impact.Originality/Relevance – The study addresses a gap in the literature by investigating the use of recycled PET in mortars through an innovative acoustic evaluation approach. It stands out for combining sustainability with technical performance, proposing the use of plastic waste as a viable alternative to conventional construction materials.Results – The results showed that increasing the PET-PCR content led to a reduction in mechanical strengths but significantly improved the acoustic performance of the mortars, particularly in impact sound insulation, indicating their potential for use in acoustic insulation applications.Theoretical/Methodological Contributions – The research demonstrates the effectiveness of Impact Acoustic Spectroscopy (IAS) as an innovative tool to evaluate the properties of cementitious materials with recycled additives. It also provides an original integration of mechanical and acoustic analyses in a single study.Social and Environmental Contributions – Replacing natural aggregates with PET-PCR helps reduce plastic waste and lessens the extraction of natural resources. The study offers a more sustainable alternative for the construction sector, with positive impacts on promoting circular economy practices and enhancing urban resilience.
Keywords: Acoustic; PCR-PET; IAS